The impact of exchange rate instability on Nigerian non-oil exports (1996)
The paper attempts to estimate the impact of exchange rate uncertainty on Nigerian non-oil exports to some of her major trading partners. Although the study generates mixed results on the impact of exchange rate instability on volume of exports, in most of the estimates there is evidence to suggest that Nigeria’s non-oil exports may have been adversely affected. The general non-significance of the exchange rate variable in the estimates also shows that the recent depreciation of the naira exchange rate may not be the overriding factor in explaining the demand for her non-oil exports. This further contradicts the claim that adopting the path of macroeconometric adjustments followed by the East Asian countries would produce the same result in all other developing countries like Nigeria.